2017
DOI: 10.1002/aoc.3750
|View full text |Cite
|
Sign up to set email alerts
|

Three novel Ni(II), VO(II) and Cr(III) mononuclear complexes encompassing potentially tridentate imine ligand: Synthesis, structural characterization, DNA interaction, antimicrobial evaluation and anticancer activity

Abstract: Three novel Cr(III),VO(II) and Ni(II) imine complexes derived from the condensation of 2‐aminophenol (AP) with 2‐hydroxynaphthaldehyde (HN) were synthesized. The prepared HNAP imine ligand and its complexes were investigated via various physicochemical tools. The results suggest that the parent ligand behaves as a dibasic tridentate ONO ligand, when coordinated to Cr(III) in octahedral and to Ni(II) in tetrahedral geometry. In the case of VO(II), it coordinates in distorted square pyramidal geometry. Also, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 42 publications
6
94
0
Order By: Relevance
“…[1][2][3] The absorption band of the C=O in the dibenzoylmethane at 1700 cm −1 persisedt even after the formation of the Schiff base ligand where the infrared spectrum of the ligand showed a stretching frequency at 1680 cm −1 , which confirmed that one of the two C=O groups only participated in the condensation. The vibrational assignments were aided by comparison with the vibrational frequencies of the related compounds.…”
Section: Ir Spectra Studymentioning
confidence: 86%
See 3 more Smart Citations
“…[1][2][3] The absorption band of the C=O in the dibenzoylmethane at 1700 cm −1 persisedt even after the formation of the Schiff base ligand where the infrared spectrum of the ligand showed a stretching frequency at 1680 cm −1 , which confirmed that one of the two C=O groups only participated in the condensation. The vibrational assignments were aided by comparison with the vibrational frequencies of the related compounds.…”
Section: Ir Spectra Studymentioning
confidence: 86%
“…[1][2][3] The vibration bands of ν(C=O) and ν(NH 2 ) that lay at 1680 and 3380 cm −1 at the parent ligand, respectively, were shifted to 1685 and 3312 cm −1 , respectively. This phenomenon appeared because of the coordination of azomethine nitrogen to ferric ion.…”
Section: Ir Spectral Studies and Mode Of Bondingmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Nowadays, the research on Schiff bases is increasing due to their ease of synthesis, structural variety, varied coordinating ability, thermal stability and catalytic activities. [5][6][7][8][9][10][11] An unsymmetric tridentate Schiff base ligand, 2-(2-nitrophenylthio)-N-((pyridine-2-yl) methylene)benzenamine, and its Mn(II), Ni(II), Cu(II) and Zn(II) complexes were synthesized and characterized using various physicochemical and spectroscopic techniques and crystal X-ray diffraction. [5][6][7][8][9][10][11] An unsymmetric tridentate Schiff base ligand, 2-(2-nitrophenylthio)-N-((pyridine-2-yl) methylene)benzenamine, and its Mn(II), Ni(II), Cu(II) and Zn(II) complexes were synthesized and characterized using various physicochemical and spectroscopic techniques and crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%